Calla Lily Beauty / Batrisyia Syafiah Hendri Dwisatrya … [et al.]. - Hendri Dwisatrya, Batrisyia Syafiah; Noor Azmi, Noor Syazliana Hanis; Mohammad Sharif, Nur Ayu Kellyna; Zulkifili, Nur Qistina; Mohamad Hussin, Nurain Nadirah
Calla Lily Beauty is a beauty company that sells organic-based beauty and skin care products, mainly lip balm and cleansing balm, that cater to all types of skin. Aligning with the vision, mission, and objectives of the business, Calla Lily Beauty strives to produce beauty and skin care products that are of high quality and meet the needs and expectations of the customers to ensure their satisfaction is at its highest when they use Calla Lily Beauty products in their daily lives. Calla Lily Beauty plays its part in adopting the concept of inclusive beauty without excluding anyone based on their skin tones, skin types, or even their shape and size. This is because Calla Lily Beauty wants all women to embrace their beauty and be confident in themselves while they bloom with beauty and glow ravishingly. Not only that, but Calla Lily Beauty also promotes the concept of sustainability and eco-friendliness through its beauty and skin care products that are made from only high-quality organic ingredients that are free from any sorts of chemicals or toxins that could easily irritate the skin. Furthermore, Calla Lily Beauty products are considered vegan as they do not contain any ingredients that are derived from animals, and the products are also not being tested on animals, thus highlighting that the products are animal cruelty-free. Most importantly, as a Muslim-owned beauty company, Calla Lily Beauty ensures that the product formulations are fully Shariah-compliant; hence, it is halal to be used by Muslims and even non-Muslims. With high-quality organic-based lip balm and cleansing balm, Calla Lily Beauty offers them at incredibly affordable and reasonable prices to potential customers, mainly females ranging from 14 to 50 years old, who would opt for eco-friendly and sustainable beauty and skin care products. These products are available at the Calla Lily Beauty store located in KL TRADERS SQUARE, Setapak, Kuala Lumpur, online platforms and retail stores. It has been noted that this would be a strategic location for Calla Lily Beauty to operate its business due to the high population density in Kuala Lumpur, which could potentially increase the success rate of the business over the years. Calla Lily Beauty is a small partnership business comprised of five individuals who occupy key roles in the organisation and are running the business together. It includes Noor Syazliana Hanis as general manager, Nur Ayu Kellyna as administrative manager, Batrisyia Syafiah as marketing manager, Nurain Nadirah as operation manager, and Nur Qistina as financial manager. Each of them holds significant responsibilities in ensuring that Calla Lily Beauty is able to achieve its goals and thrive in the industry for a long time. Calla Lily Beauty believes that by giving its best in terms of services, product quality, and marketing strategies, it will help the business to be recognized and gain more attention as one of the local brands that sells organic-based beauty and skin care products, which will increase the profits earned by the business and encourage the business to do well in the future, like developing new products or expanding the business to a larger scale.